Distinct glycan-charged phosphodolichol carriers are required for the assembly of the pentasaccharide N-linked to the Haloferax volcanii S-layer glycoprotein - Guan, Ziqiang (2010)
In Archaea, dolichol phosphates have been implicated as glycan carriers in the N-glycosylation pathway, much like their eukaryal counterparts. To clarify this relation, highly sensitive liquid chromatography/mass spectrometry was employed to detect and characterize glycan-charged phosphodolichols in the haloarchaeon Haloferax volcanii. It is reported that Hfx. volcanii contains a series of C(55) and C(60) dolichol phosphates presenting saturated isoprene subunits at the α and ω positions and sequentially modified with the first, second, third and methylated fourth sugar subunits comprising the first four subunits of the pentasaccharide N-linked to the S-layer glycoprotein, a reporter of N-glycosylation. Moreover, when this glycan-charged phosphodolichol pool was examined in cells deleted of agl genes encoding glycosyltransferases participating in N-glycosylation and previously assigned roles in adding pentasaccharide residues one-four, the composition of the lipid-linked glycans was perturbed in the identical manner as was S-layer glycoprotein N-glycosylation in these mutants. By contrast, the fifth sugar of the pentasaccharide, identified as mannose in this study, is added to a distinct dolichol phosphate carrier. This represents the first evidence that in Archaea, as in Eukarya, the oligosaccharides N-linked to glycoproteins are sequentially assembled from glycans originating from distinct phosphodolichol carriers.